Whole-Brain Imaging with Single-Cell Resolution Using Chemical Cocktails and Computational Analysis - Susaki, Etsuo A.; Tainaka, Kazuki; Perrin, Dimitri; Kishino, Fumiaki; Tawara, Takehiro; Watanabe, Tomonobu M.; Yokoyama, Chihiro; Onoe, Hirotaka; Eguchi, Megumi; Yamaguchi, Shun; Abe, Takaya; Kiyonari, Hiroshi; et al. (Cell, 2014)
Systems-level identification and analysis of cellular circuits in the brain will require the development of whole-brain imaging with single-cell resolution. To this end, we performed comprehensive chemical screening to develop a whole-brain clearing and imaging method, termed CUBIC (clear, unobstructed brain imaging cocktails and computational analysis). CUBIC is a simple and efficient method involving the immersion of brain samples in chemical mixtures containing aminoalcohols, which enables rapid whole-brain imaging with single-photon excitation microscopy. CUBIC is applicable to multicolor imaging of fluorescent proteins or immunostained samples in adult brains and is scalable from a primate brain to subcellular structures. We also developed a whole-brain cell-nuclear counterstaining protocol and a computational image analysis pipeline that, together with CUBIC reagents, enable the visualization and quantification of neural activities induced by environmental stimulation. CUBIC enables time-course expression profiling of whole adult brains with single-cell resolution. [Display omitted] •Simple and efficient brain-clearing reagents and image informatics were developed•CUBIC is applicable to imaging of fluorescent proteins in adult brains and 3D-IHC•The CUBIC method is scalable from a primate brain to subcellular structures•CUBIC enables whole-brain imaging with single-cell resolution CUBIC enables rapid whole-brain imaging with single-photon excitation microscopy and scaling from subcellular structures to a primate brain.